Peritoneal dialysis in Sichuan province of China – report from the Chinese National Renal Data System - Changwei Wu; Xiuling Chen; Amanda Ying Wang; Jin Chen; Hui Gao; Guisen Li; Li Wang; Daqing Hong (Renal Failure, 2018)
Background: Peritoneal dialysis (PD) is one of the important treatment strategies for end stage renal disease (ESRD). In this study, we aimed to study the patients on PD of Sichuan province in the registry system and to explore the risk factors. Methods: This was a retrospective study based on data from the Chinese National Renal Data System (CNRDS). The outcomes were prevalence and incidence of patients receiving PD, all-cause mortality, technical failure, end events and peritonitis. Results: This study included 2654 patients between 1 January 2010 and 31 December 2016. From 2010 to 2016, despite there were increasing numbers of patients requiring PD. Primary and secondary glomerular diseases were the main causes of ESRD. Erythropoietin, iron and antihypertensive agents were the most commonly used medications in this cohort. 12.43% of patients died and the most important cause of death was cardiac events (30.30%). The incidences of peritonitis were 0.09, 0.16, 0.11, 0.09, 0.08, 0.12 and 0.06 per patient-year, respectively. The most common etiological agent of peritonitis was staphylococcus. We divided the patients into four groups according to the incident months of peritonitis. Compared with <20 months group, the level of calcium and platelet in >60 months group were higher, and the level of ferritin in >60 months group was lower. Conclusion: Our results, representing the first largest report of peritoneal dialysis in the Southwest of China, indicated increasing numbers of patients receiving peritoneal dialysis, which will require need for medical resource.